"크리스토펠 기호"의 두 판 사이의 차이

수학노트
둘러보기로 가기 검색하러 가기
1번째 줄: 1번째 줄:
*  제1기본형식을 이용한 표현<br><math>\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}</math><br><math>\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}</math><br><math>\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}</math><br><math>\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}</math><br>
+
*  제1기본형식을 이용한 표현<br><math>\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}</math><br>  <br><math>\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}</math><br><math>\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}</math><br><math>\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}</math><br>
* <math>F=0</math> 인 경우<br><math>\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}</math><br><math>\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}</math><br><math>\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}</math><br><math>\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}</math><br><math>\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}</math><br>
+
* <math>F=0</math> 인 경우<br><math>\Gamma^1_{11}=\frac{E_u}{2E}</math><br><math>\Gamma^1_{12}=\frac{E_v}{2E}</math><br><math>\Gamma^1_{22}=\frac{-G_u}{2E}</math><br><math>\Gamma^2_{11}=\frac{-E_v}{2G}</math><br><math>\Gamma^2_{12}=\frac{G_u}{2G}</math><br><math>\Gamma^2_{22}=\frac{G_v}{2G}</math><br>

2010년 1월 11일 (월) 15:04 판

  • 제1기본형식을 이용한 표현
    \(\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}\)
     
    \(\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}\)
    \(\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}\)
    \(\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}\)
    \(\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}\)
    \(\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}\)
  • \(F=0\) 인 경우
    \(\Gamma^1_{11}=\frac{E_u}{2E}\)
    \(\Gamma^1_{12}=\frac{E_v}{2E}\)
    \(\Gamma^1_{22}=\frac{-G_u}{2E}\)
    \(\Gamma^2_{11}=\frac{-E_v}{2G}\)
    \(\Gamma^2_{12}=\frac{G_u}{2G}\)
    \(\Gamma^2_{22}=\frac{G_v}{2G}\)